THE EFFECTIVENESS OF THE REHABILITATION AND RECONSTRUCTION PROGRAM FOR POST-EARTHQUAKE COMMUNITY HOUSES IN NORTH LOMBOK REGENCY IN 2018 - Hamit, Ilhamius; Saputra, Ashar; Siswanto, M. Fauzie (Jurnal Pensil : Pendidikan Teknik Sipil, 2023)
Data published by the Government of Nusa Tenggara Barat Province in 2021, the progress of earthquake-resistant house construction in Lombok Utara Regency until July 9th, 2022, has completed 41,750 heavily damaged houses, 1,029 moderately damaged houses and 298 lightly damaged. From the data, there are still 9,040 houses whose physical progress is still in the implementation stage. This research aims to determine the effectiveness of rehabilitating and reconstructing the community houses post-Lombok Earthquake in 2018. The research method used in this research is a descriptive quantitative method with a purposive sampling technique. The research variables were taken from Perka BNPB No. 11 Tahun 2008 and adjusted with existing research objectives. The variables were Program Readiness, Program Planning, Program Implementation, and Program Monitoring and Evaluation. The sample in this research was 100 respondents from the earthquake-affected Lombok 2018 community who received earthquake-resistant house assistance and facilitators who assisted in the housing construction. Data collection in this research was conducted in Lombok Utara Regency through questionnaires, observations, and interviews. The data analysis used in this research was using the Likert scale. The research results show that the Post Disaster Community House Rehabilitation and Reconstruction Program in Lombok Utara Regency 2018 has run quite effectively. The average analysis of effectiveness using the Likert scale yields 66.83% for program readiness, 71.60% for program planning, 71.4% for program implementation, and 69.53% for program monitoring and evaluation. The average effectiveness rate produced in this research was 69.84%.